A Fishery for Modern Times: The State and the Industrialization of the Newfoundland Fishery, 1934-1968 - Muszynski, Alicja (Labour / Le Travail, 2002)
The article reviews the book, "A Fishery for Modern Times: The State and the Industrialization of the Newfoundland Fishery, 1934-1968," by Miriam Wright.